UJI EFIKASI INSEKTISIDA BERBAHAN AKTIF ALPHACYPERMETHRIN TERHADAP LALAT RUMAH MUSCA DOMESTICA DENGAN PENGASAPAN - Suwasono, Hadi; Boesri, Hasan; Priyanto, Heru; Suwaryono, Tri (Jurnal Kedokteran YARSI, 2007)
Although being of less importance to the incidence of the vector-borne disease than mosquitoes, houseflies (Musca domestica) are mechanical transmitters of the disease. The chemical control carried out until now has brought about the emergence of resistance of houseflies against DDT and many other insecticides including organophosphates and carbamates. In order to look for an alternative insecticide which can control houseflies, a study was performed on the efficacy of insecticide belonging to the synthetic pyrethroid group containing 30 g/l of the active substance such as alphacypermethrin. Four dosages of insecticide with active ingredient of 30 g/l alphacypermethrin at dosages of 17.5 ml/ha, 35 ml/ha, 50 ml/ha and 70 ml/ha respectively wereused by fogging against houseflies kept in cages. The result showed that dosages of 35 ml/ha, 50 ml/ha and 70 ml/ha were all effective to kill M. domestica.